Jauranga: una aproximación a la ocupación paracas en los valles de Palpa - Reindel, Markus (2013)
The excavations in Jauranga revealed a sequence of archaeological contexts distributed over a stratigraphy with a depth of morethan three meters. Within this stratigraphy we found the remains of numerous adobe walls pertaining to structures of a settlement dating to the Middle and Late Paracas periods. Forty nine funerary contexts from different phases of the Paracas culture were embedded in the stratified layers and structural remains. Furthermore, we recorded 31 intrusive burials of the Nasca culture.The stratigraphic analysis of the structural remains in their relation to the associated artifacts and non-artifactual finds, the ty- pological analysis of the ceramic artifacts from the stratified layers and from the burial contexts, as well as numerous radiocarbon dates allowed us for the first time to establish a chronological ordering of the developmental phases of the Paracas culture based on stratigraphic contexts. The results of these analyses helped to confirm the validity of the results of the stylistic seriation of the Paracas ceramics from the Ica valley published by Menzel, Rowe and Dawson in 1964. Based on the stratigraphic evidence recorded in Jauranga, we discuss aspects of chronology, type and function of the site, as well as their implications for the local and regional archaeological contexts.